ANALISIS USER EXPERIENCE PADA APLIKASI VOTING BERBASIS FLUTTER_: STUDI EVALUASI MENGGUNAKAN UEQ+ - Sandi A, Arif Setia (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This study aims to analyze user experience (UX) on the Muhammadiyah Paguyangan Voting Application Based on Flutter (EVoMu) to support electronic voting in selecting new leadership in the Muhammadiyah Paguyangan organization. This evaluative study employs the User Experience Questionnaire Plus (UEQ+) method, covering four main dimensions: Efficiency, Intuitive Use, Visual Aesthetic, and Trust. The author gathered data from 120 users who participated as voters in this election process. The research yielded a positive response to the EVoMu application, as evidenced by the overall scale average score exceeding 0.8. Additionally, data diversity across all scales was noted to be at a very good and acceptable level. Measurement results indicate high reliability across all scales. Trust level in the application emerges as the most influential factor in its implementation, with a mean importance rating of 2.68.